Experiences of mental health professionals providing services to adults with intellectual disabilities and mental health problems: A systematic review and meta-synthesis of qualitative research studies. (September 2022) - Ee, Jonathan; Stenfert Kroese, Biza; Rose, John
Background: Mental health professionals play an important role in providing care and treatment for adults with intellectual disabilities. A number of studies use qualitative methods to explore the experiences of these professionals and their perspectives regarding the mental health services for this population. A systematic review using meta-ethnographic approach was undertaken to summarise this research. Method: A systematic search found 14 relevant studies which were critically appraised. Key themes from these studies were extracted and synthesised. Results: Three main themes were identified: 1) Understanding the person, 2) Relational interaction and 3) Organisational factors. Conclusions: The findings of this review identified the issues mental health professionals raised in relation to their work. They described the complex presenting problems as intense yet fulfilling therapeutic relationships with their clients and their wish to improve their knowledge and skills. They identified organisational issues that need to be addressed to improve staff morale and efficiency.